Love thy neighbor : a Muslim doctor's struggle for home in rural America - Virji, Ayaz; Eisenstock, Alan (New York crown Publishing, 2019)
"A powerful true story about a Muslim doctor's service to a small town and the hope of overcoming our country's climate of hostility and fear. In 2013, Dr. Ayaz Virji left a comfortable job at an East Coast hospital and moved to a town of 1,400 in Minnesota, feeling called to address the shortage of doctors in rural America. But in 2016, this decision was tested when the reliably blue, working-class county swung for Donald Trump. Virji watched in horror as his children faced anti-Muslim remarks at school and some of his most loyal patients began questioning whether he belonged in the community. Virji wanted out. But in 2017, just as he was lining up a job in Dubai, a local pastor invited him to speak at her church and address misconceptions about what Muslims practice and believe. That invitation has grown into a well-attended lecture series that has changed hearts and minds across the state, while giving Virji a new vocation that he never would have expected. In [this book], Virji relates this story in a gripping, unforgettable narrative that shows the human consequences of our toxic politics, the power of faith and personal conviction, and the potential for a renewal of understanding in America's heartland."--Dust jacket.
Tough questions -- Where am I? -- Dignified medicine -- Jihad -- Fallout -- Logic and sincerity -- Faith is what you do -- "Islam supports terrorism" -- Her choice, not mine -- Sharia law -- Breathe -- What will it take?
Keywords: Virji, Ayaz; Muslim physicians -- United States -- Biography; Physicians -- United States -- Biography; Muslims -- United States -- Biography; Islam -- Relations -- United States -- Christianity; Christianity and other religions -- Islam; Biography / Autobiography; Personal Memoirs; Ethnic Studies - General; Religious Intolerance, Persecution & Conflict; RELIGION / Islam / General; SOCIAL SCIENCE / Discrimination & Race Relations; BIOGRAPHY & AUTOBIOGRAPHY / Religious; BIOGRAPHY & AUTOBIOGRAPHY / Social Activists; United States -- Politics and government -- 21st century; Autobiographies